2015
DOI: 10.1080/10286020.2015.1043902
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive prenylated xanthones from the stems ofCratoxylum cochinchinense

Abstract: Cochinchinones M-U (1-9), together with 12 known compounds (10-21), were isolated from the stems of Cratoxylum cochinchinense (Lour.) Blume. Their structures were determined on the basis of extensive spectroscopic data analyses. In addition, their retinoid X receptor-α transcriptional activities were evaluated using an in vitro assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…C. cochinchinense is rich in chemical constituents such as xanthones, flavonoids, tocotrienols, triterpenoids and benzophenones, anthraquinones [14,[17][18][19][20][21][22][23]. It has been reported that xanthones are in fact the most abundant biologically active secondary metabolites in C. cochinchinense [14].…”
Section: Introductionmentioning
confidence: 99%
“…C. cochinchinense is rich in chemical constituents such as xanthones, flavonoids, tocotrienols, triterpenoids and benzophenones, anthraquinones [14,[17][18][19][20][21][22][23]. It has been reported that xanthones are in fact the most abundant biologically active secondary metabolites in C. cochinchinense [14].…”
Section: Introductionmentioning
confidence: 99%
“…There are two species and one subspecies in China, mainly growing in Guangdong, Guangxi, and Yunnan provinces or regions [ 1 ]. Previous chemical investigations on the plants from the genus Cratoxylum have caused the isolation and identification of a variety of natural products including xanthones [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], triterpenoids [ 2 ], tocotrienols [ 2 ], bisanthraquinones [ 3 ], phloroglucinol benzophenones [ 15 ], and anthraquinobenzophenones [ 3 ], which display various biological activities, such as anti-tumor [ 3 , 6 , 8 , 9 , 10 , 14 ], anti-inflammatory [ 10 , 15 ], anti-bacterial [ 8 , 12 ], anti-oxidant [ 7 , 12 ], anti-malarial [ 6 , 9 ], anti-HIV [ 4 ], α -glucosidase inhibitory [ 15 ], vascular protective [ 7 ], retinoid X receptor -α transcriptional [ 11 ], protein tyrosine phosphatase 1B inhibitory [ 13 ], and NF- κ B inhibitory activities [ 10 ]. Among the genus Cratoxylum , C. cochinchinense (Lour.)…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary experimental results revealed that the 85% ethanol extract of the stems and leaves of C. cochinchinense showed notable inhibitory effect against nitric oxide (NO) production induced by lipopolysaccharide in mouse macrophage RAW 264.7 cells with an IC 50 value of 9.68 ± 0.12 μg/mL in vitro, as well as anti-HIV-1 reverse transcriptase (RT) effect with an EC 50 value of 7.19 μg/mL. To fully explore the enormous potential of Hainan’s unique tropical medicinal plants and tropical fruits in the prevention and treatment of major human diseases, in the course of our continuing investigation of biologically active and structurally diverse natural products from the tropical medicinal plants and tropical fruits [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], a phytochemical study on the stems and leaves of C. cochinchinense was thus undertaken and led to the isolation and characterization of four new xanthones, cratocochinones A–D ( 1 – 4 ),which are a kind of rare natural product with extensive biological activities [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], alongside eight known analogues 5 – 12 . Their chemical structures were determined on the basis of comprehensive spectral analyses.…”
Section: Introductionmentioning
confidence: 99%
“…As a deciduous shrub or tree, Cratoxylum cochinchinense belongs to the Clusiaceae plant family, in which some species have been used historically as traditional medicines ( Duan et al, 2012 ). Previous phytochemical investigations have indicated that the plants of Cratoxylum genus are rich in xanthones with extensive biological activities including anti-malaria, anti-bacteria, anti-HIV, and cytotoxicity ( Laphookhieo et al, 2006 ; Laphookhieo et al, 2009 ; Rattanaburi et al, 2014 ; Duan et al, 2015 ; Ito et al, 2017 ; Li et al, 2018 ; Huang et al, 2019 ; Jia et al, 2019 ; Lv et al, 2019 ). Some xanthones, e.g., gambogic acid, were found to have promising cytotoxic effects and be potentially useful for the discovery of anticancer lead compounds.…”
Section: Introductionmentioning
confidence: 99%